Innovative ingredients and emerging technologies for controlling ice recrystallisation, texture and structure stability in frozen dairy desserts: a review - Soukoulis, Christos; Fisk, Ian D. (Taylor & Francis, 2016)
Over the past decade, ice cream manufacturers have developed a strong understanding of the functionality of key ingredients and processing, developing effective explanations for the link between structure forming agents, stability mechanisms and perceived quality. Increasing demand for products perceived as healthier / more natural with minimal processing has identified a number of new tools to improve quality and storage stability of frozen dairy desserts. Ingredients such as dietary fibre, polysaccharides, prebiotics, alternate sweeteners, fat sources rich in unsaturated fatty acids and ice structuring proteins have been successfully applied as cryoprotective, texturizing and structuring agents. Emerging minimal processing technologies including hydrostatic pressure processing, ultrasonic or high pressure assisted freezing, low temperature extrusion and enzymatically induced biopolymers crosslinking have been evaluated for their ability to improve colloidal stability, texture and sensory quality. It is therefore timely for a comprehensive review.